INFLUENCE OF NEW CONSTRUCTION PROJECTS ON VINOHRADY TUNNELS - Jiří Barták (Acta Polytechnica CTU Proceedings)
After demolition of the brutalist architectural style Transgas building in Vinohradská Street, Prague, (all buildings of which were located above the historic Vinohrady tunnels II and III), there will be built the Vinohradská Administration Centre with the addition of a building No. 345 called "Above the Museum". Both buildings have the foundation joint immediately above the lining of the existing tunnels. This paper describes the main phases of construction and the character and size of the deformation affecting the stone block lining of the tunnels.